(untitled) (Research, Society and Development, 2021)
The objective of this work was to rank urban macrodrainage alternatives in Sub-basin 2 of the Estrada Nova Hydrographic Basin (BHEN) in Belém-PA, Amazonia, Brazil, to aid in the selection of an alternative to be implemented. The methodology used considered technical, environmental and economic criteria, and was applied to five possible alternatives for the functionality of the Sub-basin under study, which were developed using the free computational code Storm Water Management Model (SWMM). The modeling considered precipitation of 50 years of return, tides, lengths, sections of channels, existing galleries and bridges, Manning coefficients, availability of areas to implement components necessary for the system’s functionality, such as new channels, storage units and floodgates. Amongst the five alternatives, the second alternative resulted in the best ranking, which considers agreement of sections and storage unit. Thus, the results obtained were very promising and confirmed the expectation for the use of better rainwater management practices, with the methodology used allowing the problem to be solved very satisfactorily.